Strengthening Environmental Criminal Law In Regional Development Policy - Hidayatulloh, Syarif (Jurnal Justiciabelen, 2024)
Human rights cover various fields, not only economics and politics, but also in the field of providing the need for a good and healthy living environment. The living environment is life that encompasses the order and values of life that exist within it. Orders and values that maintain the sustainability of the environment and natural resources and social justice for human life regarding HAL (Environmental Rights) remain for today and future generations. The study of the environment is an issue that is interrelated with development. The consideration that encourages the integration of environment and development is the impact of balance on the environment’s ability to support sustainable development. The research results are an answer to regional development policy problems which show a lack of involvement of environmental legal principles so that attention needs to be paid so that a region can develop without disturbing the existing environmental ecosystem. The method used is the normative juridical method, namely research that uses statutory regulations as a basis for solving the problems raised. The data collection method used in this research is library research. Meanwhile, the data analysis used is qualitative, the analysis is by describing the data in a quality manner in the form of sentences that are orderly, coherent, logical, non-overlapping and effective, making it easier to interpret data and analyze.